The Hummocky Patches and Associated Sediment Dynamics Over an Accretional Intertidal Flat - Zhu, Shibing; Chen, Yining; Yan, Weibing; Xing, Fei; Li, Renzhi; Li, Mingliang; Shi, Benwei; Wang, Ya Ping (Frontiers in Earth Science, 2022)
Tidal flat system is composed of multiple sub-scale geomorphological units. We found a new mesoscale geomorphological unit on sand-mud mixed intertidal zone along China coast, which was defined as hummocky patches. Hummock patches are most developed in middle tidal flat, with horizontal magnitude of 10-20 m and vertical magnitude of ~15 cm. Hummocky patches significantly influence local sediment transport, thus affect morphological evolution of tidal flats. In order to understand the formation and development mechanisms of hummocky patches, we collected hydrodynamics, topography, sediment properties, and substrate erosion thresholds data through an in-situ field observation covering a spring-neap tidal cycle over an accretional intertidal flat in Jiangsu, China. We found that sediment characteristics including sorting coefficient (σ: measuring the uniformity of sediment particles) and silt/clay/organic matter/water content are essentially different between hummocky patches and nearby seabed, which leads to spatially varied substrate erosion resistance. The measured erosion thresholds for patches are two times higher comparing to surrounding seabed sediment, which provides foundation for the formation of hummocky patches. Under the impact of periodical tidal currents and waves, surrounding seabed experiences considerably more erosion than patch area, which finally develops to hummocky patches. Therefore, hydrodynamic forces drive the formation and development of patches. The erosion resistance of patches decreases vertically from seabed surface to sublayer, causing initial erosion in the lower sublayer, followed by a mass collapse of the seabed surface layer. Hummocky patches are commonly found in middle tidal zone and their sizes decrease to the shore as tidal currents and waves attenuate with shoreward propagation. Hummocky patches have distinct seasonal variations, which only appear in summer and autumn when wind waves are comparatively low than winter and spring. We infer the reason is that the strong hydrodynamics caused by winter storms cause larger bottom shear stress than the erosion threshold of hummocky patches, leading to destruction of hummocky patches and a smooth tidal flat surface. This study shed new insight on the knowledge of mesoscale geomorphological units and their formation and development in intertidal flats, which provides crucial information for developing more realistic tidal flat sediment transport and morphological models.